2009
DOI: 10.1007/s11605-009-0997-1
|View full text |Cite
|
Sign up to set email alerts
|

Sleeve Gastrectomy Provides a Better Control of Diabetes by Decreasing Ghrelin in the Diabetic Goto–Kakizaki Rats

Abstract: SG shows better control in terms of glucose tolerance and other measurements. This study provides direct evidence that SG possesses better improvement of diabetes by reduction of Ghrelin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 39 publications
(45 reference statements)
5
24
0
Order By: Relevance
“…In rodents, Shin et al 35 saw greater suppression of acylated ghrelin, the active form of ghrelin, in response to meal, similar to what has been seen in a T2DM rodent model that underwent the VSG procedure. 36 Similar decreases in postprandial total ghrelin were also seen between RYGB and VSG 1 week and 3 months postoperatively. 23 However, other studies have not shown any changes in fasting or mealinduced total ghrelin levels in RYGB patients, 27,37 but still showed significant decreases in patients with VSG.…”
Section: Changes In Gut Hormonesmentioning
confidence: 59%
“…In rodents, Shin et al 35 saw greater suppression of acylated ghrelin, the active form of ghrelin, in response to meal, similar to what has been seen in a T2DM rodent model that underwent the VSG procedure. 36 Similar decreases in postprandial total ghrelin were also seen between RYGB and VSG 1 week and 3 months postoperatively. 23 However, other studies have not shown any changes in fasting or mealinduced total ghrelin levels in RYGB patients, 27,37 but still showed significant decreases in patients with VSG.…”
Section: Changes In Gut Hormonesmentioning
confidence: 59%
“…Previous studies in experimental rat models of SG have shown a decrease in body weight compared to the respective control group [16][17][18][19][20][21][22][23], although not statistically significant in all cases. SG represents a bariatric surgery procedure that involves the reduction of the total stomach size and lumen through the removal of gastric tissue along the greater curvature of the stomach from the fundus to the antrum.…”
Section: Discussionmentioning
confidence: 78%
“…SG experimental models have been successfully carried out in diverse species, mainly pigs and rats, providing evidence of the effects on weight reduction and comorbidity improvement [12,[14][15][16][17][18][19][20][21][22][23]. The beneficial impact of this restrictive surgical procedure has been shown in physiological circumstances, diet-induced, and genetic obesity as well as in different type 2 diabetes experimental models.…”
Section: Introductionmentioning
confidence: 99%
“…PYY exerts its action through NPY receptors, decreases gastric motility in response to food ingestion and induces satiety [25][26][27][28]. Further it is documented that PYY shows a close relation to insulin resistance and insulin secretion [29][30].…”
Section: Sleeve Gastrectomy and Its Mode Of Action On Weight Lossmentioning
confidence: 99%